PELATIHAN COMMUNITY MENTAL HEALTH NURSING (CMHN) BAGI PERAWAT DAPAT MENINGKATKAN PENANGANAN MASALAH KESEHATAN JIWA DI MASYARAKAT - Ismailinar Ismailinar; Sulaiman Sulaiman; Putro Simeulu (Poltekkes Kemenkes Aceh, 2023)
Community-based psychiatric nursing care is a nursing approach to mental patients, which is carried out directly to patients and their families at home by health center nurses who have received previous training. Nurses who have been trained are expected to have competence, one of which is being able to provide nursing care to patients with mental disorders in the community, so that patients with mental disorders can be handled optimally. This research is to see the relationship between the Effectiveness of CMHN Training Implementation in 31 Public Health Centers in North Aceh District. The study was conducted at 31 Community Health Centers in North Aceh District. The research design used a correlational design with a total sampling technique. Data collection was carried out by distributing questionnaires online via the Google form to respondents in July 2022. Data analysis used the Chi Squere test with a 95% confidence interval. The research results obtained p value = 0.000, α = 0.05, p value ≤0.05, the statistical results are significant, meaning that there is a relationship between the effectiveness of implementing CMHN training on improving the handling of mental health problems in North Aceh District.